LINGUISTIC FEATURE OF MEDICAL ADVERTISEMENTS (ResearchJet Journal of Analysis and Inventions, 2021)
This article examines the linguistic and social aspects of medical advertising. Their progmalinguistic features were evaluated.Linguistic and social aspects of medical advertisements have been studied in this article. Their Progmalingvistic peculiarities have been assessed.